Technical note monitoring native vegetation on a dumpsite of PCB-contaminated soil - Pavlíková, Daniela; Macek, Tomas; Macková, Martina; Pavlík, Milan (International journal of phytoremediation, 2007)
Composition of native vegetation on a polychlorinated biphenyls (PCB)-contaminated soil dumpsite at Lhenice, South Bohemia (Czech Republic), was determined and species variability in the accumulation of PCBs in plant biomass was investigated. Soil stripping contaminated by PCBs originated at a factory producing electrical transformers that mostly used the commercial PCB mixture Delor 103 and 106. The PCB content of soil in the most contaminated part of the dumpsite reached 153 mg kg(-1) dry soil. Low diversity of plant species was found on the dumpsite. Results showed three grass species, Festuca arundinacea Schreb., Phalaroides arundinacea (L.) Rauschert., and Calamagrostis epigeios (L.) Roth., to be the major components of the vegetation and confirmed their high tolerance toward PCB contamination. The highest content of PCB in plant biomass--813.2 microg kg(-1) dry biomass--was determined in Festuca aboveground biomass. For phytoextraction purposes especially, Festuca can be recommended due to its high biomass yield, but its bioconcentration factor was very low (0.006). Tripleurospermum maritimum (L.) Sch. Bip. and Cirsium arvense (L.) Scop. grew mainly at the margins of the most contaminated part of the dumpsite. The PCB content determined in their aboveground biomass-278.7 and 289.5 microg kg(-1) dry biomass, respectively--was nonsignificantly lower compared to grass species Phalaroides and Calamagrostis. Salix (Salix viminalis L. and Salix caprea L.) was monitored among plant species composition at this site as a representative of woody species.
Keywords: Soil Pollutants; Česká republika; rostliny; Plant Development; Plants; Czech Republic; Environmental Monitoring; Polychlorinated Biphenyls; Biodegradation, Environmental; Plant Extracts; látky znečišťující půdu; polychlorované bifenyly; vývoj rostlin; monitorování životního prostředí; rostlinné extrakty; biodegradace